Unfinished business : Union ordination votes 10 years in review. - Wibberding, Jim
Maud was ready to lead, but was the church ready for her? The mission of Adventism caught her heart at age 11, while she watched the pioneers organize their movement at Battle Creek in 1863. Her passion drew her to the publishing work when she was 16 years old. Maud enjoyed coming of age in the shadow of Adventist giants, but she tired of the glass ceiling. A woman of vision with a knack for details, she chafed at being "the help" when she knew she could lead.